Mengoptimalkan Akurasi Navigasi dan Fleksibilitas Pembayaran pada Aplikasi Maxim : Tinjauan terhadap Pengalaman Pengguna - Farahsalsabil Yudhiane Cantika; R. Yuniardi Rusdianto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Maxim is an online transportation service that is often used by people in Indonesia by offering various services including Maxim Ride, Maxim Car, Maxim Delivery, Maxim Food, and Maxim Cargo. Maxim also offers cheap fares start three kilometers on every service used by the community so that it can attract people's interest in using it, it is also supported by Maxim who continues to exist in various regions of Indonesia to enjoy the online transportation service. However, it is possible that there are still problems when users use the service, namely the accuracy of the lacking maps and the less variable payment method. So there needs to be optimization on navigation accuracy and payment flexibility in Maxim application.Therefore, through the MSIB Batch 4 Program of Certified Independent Studies on Product Management Fundamentals for Digital Product at Apiary Academy, The researchers applied the study to Maxim's application in the form of a Final Project supported by a qualitative descriptive research method through a survey and in dep depth interview to find out more details about the user's problems for navigation accuracy planning and flexibility payments can be maximally accepted by the public especially today's users. Navigation Accuracy,Payment Flexibility, Maxim, User Experience